Etiologies of uterine malformations. Issue 8 (8th June 2016) - Jacquinet, Adeline; Millar, Debra; Lehman, Anna
Abstract : Ranging from aplastic uterus (including Mayer–Rokitansky–Kuster–Hauser syndrome) to incomplete septate uterus, uterine malformations as a group are relatively frequent in the general population. Specific causes remain largely unknown. Although most occurrences ostensibly seem sporadic, familial recurrences have been observed, which strongly implicate genetic factors. Through the study of animal models, human syndromes, and structural chromosomal variation, several candidate genes have been proposed and subsequently tested with targeted methods in series of individuals with isolated, non‐isolated, or syndromic uterine malformations. To date, a few genes have garnered strong evidence of causality, mainly in syndromic presentations ( HNF1B, WNT4, WNT7A, HOXA13 ). Sequencing of candidate genes in series of individuals with isolated uterine abnormalities has been able to suggest an association for several genes, but confirmation of a strong causative effect is still lacking for the majority of them. We review the current state of knowledge about the developmental origins of uterine malformations, with a focus on the genetic variants that have been implicated or associated with these conditions in humans, and we discuss potential reasons for the high rate of negative results. The evidence for various environmental and epigenetic factors is also reviewed. © 2016 Wiley Periodicals, Inc.